Judicial limits over the administrative discretionary act: analysis of the decisions of the injunctions granted in aco 3.451/DF by the Brazilian Supreme Court - Azevedo, Edgar Meira Pires de; D’Assunção, Maria Esther Alencar Advíncula; Presgrave, Ana Beatriz Ferreira Rebello (Revista Internacional Consinter de Direito, 2023)
The serious health situation resulting from the Covid-19 pandemic, in addition to the global health emergency, also generated deep crises in the economic, political-ideological and governance fields, which led to the Judiciary several issues that, in a normal situation, would not be within its jurisdiction. Therefore, this paper aims to address the decision rendered by the Federal Supreme Court (STF) in ACO 3.451/DF, in which the Court allowed the automatic authorization for the State of Maranhão to import and distribute the Sputnik V vaccine for its population. Consequently, the central problem of this research is to analyze whether this position, in addition to promoting a re-reading of the control of the administrative act by the Judiciary, is in accordance with the constitutional provisions. This is a research of strategic basic purpose, descriptive and exploratory objective, under the deductive method, with a qualitative approach and performed through bibliographic and documental procedures. In the end, it is verified that the decision taken by the STF in the judgment of ACO 3451/DF affronts the principle of the functional division of power, expressed in art. 2 of the Federal Constitution, and also culminates in violating the right to health itself, set forth in art. 196 of the Constitution. Moreover, the greatest contribution of the research is, precisely, in enabling the discussion of the position adopted by the Court before the ineffective management of the Executive due to the health crisis that has been established with the Covid-19 pandemic.